The Dog that Didn’t Bark : The Missed Opportunity of Africa’s Resource Boom - Cust, James; Ballesteros, Alexis Rivera; Zeufack, Albert (Washington, DC : World Bank, 2022)
The commodity price boom from 2004–2014 was a huge economic opportunity for African countries abundant in oil, gas and minerals. During this period their government revenues from resources grew by an average of 1.1 billion US$ per year, and economic growth in those same resource-rich countries surged. GDP growth in resource-rich countries accelerated from 4.6% to 5.4% as countries entered a decade long period of sustained high commodity prices. Nonetheless, the paper traces a significant missed opportunity for resource-rich countries in Africa, with little to show for it in the post-boom period, which saw growth collapse far below pre-boom levels, to 2.7% per annum. This paper considers the record of performance during the boom (2004–2014) and subsequent bust from 2015 onwards. The paper describes four main outcomes of the boom: 1) measures of resource dependency rose in Sub-Saharan Africa during the boom, 2) the growth record was strong during the boom but collapsed once commodity prices fell, 3) poverty and inequality rose during the boom despite strong GDP growth, 4) resource-rich countries failed to diversify both their exports and their asset base, leaving them poorly prepared for the end of the boom and a period of lower commodity prices and subsequent COVID-19 pandemic. The conclusions are stark. During this golden decade of sustained high commodity prices and booming revenues, there was limited re-investment of those revenues into building sustainable assets for the future. In other words, countries consumed the boom, rather than successfully transformed their economies. The conclusion is that many resource-rich countries in the region squandered their “once in a generation” opportunity for economic transformation, offering policy lessons that may prove valuable as we enter a new period of elevated commodity prices.